Physoschistura dikrongensis, a new loach from Arunachal Pradesh, India (Teleostei: Nemacheilidae) - Lokeshwor, Y.; Vishwanath, W. (Zootaxa, 2012)
A new species of nemacheilid, Physoschistura dikrongensis, is described from the Brahmaputra basin in ArunachalPradesh, India. It is easily distinguishable from congeners in having two V-shaped dark brown bars across the caudal fintowards the distal end; 11–15 irregular bars on the body; dark brown mottled markings on the head; 4 simple and 8½branched dorsal-fin rays; 4 simple anal-fin rays; an incomplete lateral line; a forked caudal fin with 8+7 branched rays; a well-developed axillary pelvic lobe; suborbital flap in males, and nine preoperculo-mandibular sensory canal pores.